2020
DOI: 10.1111/jcmm.14911
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 expression promoted by Poly(I:C) in cervical cancer cells regulates cytokine expression and recruitment of macrophages

Abstract: | INTRODUC TI ONCervical cancer is the most common gynaecological malignancy, ranking fourth in both incidence and cancer-related deaths among women worldwide. 1 Despite the advancements in prophylactic vaccines and screening programs, which have greatly decreased the incidence rate, effective therapies continue to fall short. A therapeutic vaccine, however, would likely be a promising approach in the treatment of cervical cancer by modulating the host immune system in vivo and thus provoking an anti-tumour re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Previous studies reported that tumor cells could produce numerous chemokines to attract macrophages, which further dictate the fate of tumor developing and progression through secreting an assorted array of cytokines. It is well-established that IL6 is an essential chemokine for the recruitment of macrophages in cancers (30, 32), such as cervical cancer and prostate cancer. Accordingly, we further evaluated whether HSPB1 could modulate the infiltration of macrophage in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that tumor cells could produce numerous chemokines to attract macrophages, which further dictate the fate of tumor developing and progression through secreting an assorted array of cytokines. It is well-established that IL6 is an essential chemokine for the recruitment of macrophages in cancers (30, 32), such as cervical cancer and prostate cancer. Accordingly, we further evaluated whether HSPB1 could modulate the infiltration of macrophage in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunction of the antitumor immune system is closely related to CC development and progression ( Chen Z. et al, 2019 ; Liu J. J. et al, 2020 ; Liu X. et al, 2020 ). High levels of activated memory CD4+T cells predict a better prognosis in patients with CC ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interplay between HPV-infected host cells and the local CVM may determine the course of cervical carcinogenesis. The microbiome in the local CVM can modulate immune responses, including critical components of antitumor immunity, thereby contributing to the therapeutic activity of immune checkpoint inhibitors ( 12 ). However, crosstalk between the local vaginal microbiome and the CVM during cervical carcinogenesis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the degradation of innate defenses may occur ( 5, 25 ). In addition, persistent chronic inflammation may lead to anti-inflammatory effects and regulate the expression of cytokines, such as IL6, which may increase the risk of cytologic abnormalities ( 12 ). In previous research by the authors of the current study, it was observed that chronic inflammation (graded by inflammatory cell count) significantly increased the risk of cytologic abnormalities ( 28 ).…”
Section: Discussionmentioning
confidence: 99%